A methodological rejoinder to "Does income relate to health due to psychosocial or material factors?" - Oded Stark; Marcin Jakubek (University of Tübingen, Faculty of Economics and Social Sciences, 2020)
There is a presumption that when an individual's comparison of his income with the incomes of others in his comparison group yields an unfavorable outcome, the individual is dismayed and experiences stress that impinges negatively on his health. In a recent study, Hounkpatin et al. (2016) conduct an inquiry aimed at deciphering which measure of low relative income reflects better the adverse psychosocial effect of low relative income on health. Hounkpatin et al. pit against each other two indices that they characterize as 'competing:' the 'relative deprivation (Yitzhaki Index)' of individual i, RD i; and the 'income rank position' of individual i, R i. In this Rejoinder we show that because a measure of rank is embodied in the RD i index and the R i index can be elicited from the RD i index, these two indices need not be viewed as competing. Furthermore, we formulate a composite measure of relative deprivation, CRD i, which can be used to assess more fully the psychosocial effect of individual i's low relative income on his health.
urn:nbn:de:bsz:21-dspace-1004417
Keywords: I12; I14; I18; 330; The adverse psychosocial effect of low relative income on health; An index of relative deprivation; An index of income rank; Decomposition of the index of relative deprivation into ordinal and cardinal components; A composite measure of relative deprivation